2011
DOI: 10.1038/labinvest.2011.102
|View full text |Cite
|
Sign up to set email alerts
|

Intrarectal administration of oxygenated perfluorodecalin promotes healing of murine colitis by targeting inflammatory hypoxia

Abstract: Intestinal inflammation is associated with enhanced mucosal hypoxia, which contributes to the ongoing inflammatory process and hampers appropriate mucosal healing. We questioned whether local treatment with an oxygen (O 2 )-carrying and -releasing molecule (oxygenated perfluorodecalin, O 2 -PFD) could positively influence the course of experimental colitis. The impact of intrarectal (IR) treatment with O 2 -PFD was tested using the murine dextran sodium sulfate (DSS)-induced model of distal colitis, both in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It is reasonable to assume that the molecular mechanisms that fine-tune the hypoxia-inflammation circle represent attractive targets for the treatment of chronic, nonresolving inflammation. The latter notion is further supported by alleviation of experimental colitis via delivery of oxygen [ 21 , 22 ].…”
Section: Inflammation and Hypoxiamentioning
confidence: 99%
“…It is reasonable to assume that the molecular mechanisms that fine-tune the hypoxia-inflammation circle represent attractive targets for the treatment of chronic, nonresolving inflammation. The latter notion is further supported by alleviation of experimental colitis via delivery of oxygen [ 21 , 22 ].…”
Section: Inflammation and Hypoxiamentioning
confidence: 99%
“…Hypoxia in the colonic mucosa significantly inhibits the normal aerobic oxidation of glucose and increases the anaerobic glycolysis in cmECs (23). Additionally, research has shown that with the aggravation of hypoxia in the colonic mucosa, the apoptosis and necrosis of cmECs increase significantly, both of which are positively correlated to the severity of UC (24,25). This study showed that intracellular glycolysis in cmECs was significantly enhanced, and hypoxia was aggravated in the colonic mucosa in colitis.…”
Section: Discussionmentioning
confidence: 52%
“…In 15 rats with LCA ligation, we administered a single dose (0.6 mL/kg) of 2% DDFPe intravenously at 10 min after LCA ligation. The treatment dose was derived from that used in animal models reported previously [3-6,8-12]. The dose and administration schedules were preliminarily verified in our pilot studies, in which no adverse events, such as animal death or difficulty in recovery from surgery and anesthesia, were encountered.…”
Section: Methodsmentioning
confidence: 99%
“…Such properties allow DDFPe to deliver many times the oxygen content of liquid perfluorocarbon and can compensate for up to 90% of the oxygen deficiency. Significant reduction of cerebral infarct size in rat and rabbit stroke models has been achieved by single or repeated doses of DDFPe [4-6,8-14]. In a study of a mouse model with MI, caused by irreversible permanent occlusion of the left anterior descending (LAD) coronary artery, DDFPe was administered prior to the coronary occlusion and shown to be able to elicit a cardioprotective effect that persisted well beyond the assumed elimination time of DDFPe [3].…”
Section: Introductionmentioning
confidence: 99%